What Makes a Norm Robust: The Norm Against Female Combat. Issue 1 (20th February 2019) - Percy, Sarah
Abstract: The norm against female combat participation has been powerfully influential and extremely slow to change, despite a record of violation and concerted attempts by states to overturn it. As a result, it is a useful lens through which to examine the factors that make norms robust. I examine two junctures for where the norm has been tested but not overturned: World War II and the slow shift by some states to incorporate women into their militaries beginning in the 1980s. These instances reveal two important elements of norm robustness: (1) the degree to which norms are embedded with other norms is essential to understanding why the norm gained strength after women participated in World War II, and (2) the absence of legalization and norm entrepreneurs explains why the integration of women in the 1980s and onward has not overturned the norm. The article also examines other features of norm robustness, particularly the notion that norms that are both procedural and ethical in character will be more robust, and that the behaviour of powerful states does not always cause norm diffusion through the international system.